Assessment of Utilization of Social Network in Learning Mathematics among Pre-Service Teachers in Colleges of Education in Kano State, Nigeria - YAKUBU, Lawan; HARUNA, Auwalu; MUHAMMAD, Fatuhu; HAMISU, Binta Tafashiya (Ilorin Journal of Education, 2024)
This study investigated pre-service mathematics teachers’ level of utilization of social network in learning mathematics in Colleges of Education (COEs) in Kano state, Nigeria. The study adopted the descriptive survey design. A sample of two COEs, one Federal Government - owned and one State-owned, were randomly selected by simple random sampling technique. From the two COEs, a sample of 126 mathematics pre-service teachers made up of 67 males and 59 females was then selected using cluster sampling technique. A structured questionnaire (Pre- Service Mathematics Teachers Social Network Utilization Questionnaire) was used to collect data. The questionnaire had an internal consistency reliability index of 0.76 obtained by Cronbach Alpha method. The data collected was analyzed using mean to answer the research questions while t-test was used to test the formulated hypotheses at 0.05 α- level. Results indicated that pre-service mathematics teachers in COEs utilized Facebook, WhatsApp, Instagram, TikTokand Snapchat to learn mathematics most often among all other social network sites and that male students use social network sites for the purpose of learning mathematics more often when compared to female students. It was recommended that Pre-service teachers in COEs should be encouraged by course lecturers to use Social Media Network Sites (SMNSs) to learn mathematics by giving online assignments.